2019
DOI: 10.1007/s40261-019-00857-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Macitentan on the Pharmacokinetics of the Breast Cancer Resistance Protein Substrates, Rosuvastatin and Riociguat, in Healthy Male Subjects

Abstract: BackgroundMacitentan is a clinically approved endothelin receptor antagonist for the treatment of pulmonary arterial hypertension (PAH). Increasing use of combination drug therapy in PAH means that it is important to recognize potential drug–drug interactions (DDIs) that could affect the efficacy and safety of macitentan in patients with PAH.ObjectiveTwo Phase 1 studies were conducted to investigate the effect of macitentan at steady-state on the pharmacokinetics of the breast cancer resistance protein (BCRP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Moreover, aprocitentan exhibited 50% inhibition of the breast cancer resistance protein (BCRP) in vitro. Given that rosuvastatin is a substrate of organic anion‐transporting polypeptide and BCRP transporters, a single‐center, open‐label, single‐sequence, phase 1 study (NCT03245229) demonstrated that rosuvastatin did not influence plasma concentrations of aprocitentan 25,26 …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, aprocitentan exhibited 50% inhibition of the breast cancer resistance protein (BCRP) in vitro. Given that rosuvastatin is a substrate of organic anion‐transporting polypeptide and BCRP transporters, a single‐center, open‐label, single‐sequence, phase 1 study (NCT03245229) demonstrated that rosuvastatin did not influence plasma concentrations of aprocitentan 25,26 …”
Section: Introductionmentioning
confidence: 99%
“…Rosuvastatin, a 3‐hydroxy‐3‐methyl‐glutaryl‐coenzyme A reductase inhibitor indicated for the treatment of hypercholesterolemia in the dose range of 5 to 40 mg is a substrate of various transporter proteins including BCRP and organic anion‐transporting polypeptides 11‐13 . Rosuvastatin was specifically selected, as it has also been used in the investigation of BCRP inhibition by another ERA, macitentan, of which aprocitentan was identified as a metabolite 14 . Additionally, rosuvastatin is a treatment of interest in the target population as patients with resistant hypertension have comorbid diseases such as chronic kidney disease, which often is associated with hypercholesterolemia 15 …”
mentioning
confidence: 99%
“…[11][12][13] Rosuvastatin was specifically selected, as it has also been used in the investigation of BCRP inhibition by another ERA, macitentan, of which aprocitentan was identified as a metabolite. 14 Additionally, rosuvastatin is a treatment of interest in the target population as patients with resistant hypertension have comorbid diseases such as chronic kidney disease, which often is associated with hypercholesterolemia. 15…”
mentioning
confidence: 99%